2011
DOI: 10.1002/jsfa.4339
|View full text |Cite
|
Sign up to set email alerts
|

Some characteristics and functional properties of rapeseed protein prepared by ultrasonication, ultrafiltration and isoelectric precipitation

Abstract: Ultrasonication and ultrafiltration were significantly better than the traditional method of rapeseed protein extraction. The ultrafiltered rapeseed protein RPs had superior functional properties. The results of this study provide useful indicators for rapeseed protein as a potential replacement for other proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(46 citation statements)
references
References 27 publications
8
38
0
Order By: Relevance
“…The decrease of particle size after ultrasonic pretreatments might be attributed to the cavitation and micro-streaming forces resulting from the ultrasound, which could disrupt noncovalent bonds between SPI molecules Hu et al (2013c). It also might be probably ascribed to the dissociation of macromolecular protein by ultrasound during heating (Dong et al 2011). This was in accord with the results of Jambrak et al (2009) who had already reported that ultrasonic pretreatments could change the particle size of proteins.…”
Section: Particle Sizesupporting
confidence: 79%
“…The decrease of particle size after ultrasonic pretreatments might be attributed to the cavitation and micro-streaming forces resulting from the ultrasound, which could disrupt noncovalent bonds between SPI molecules Hu et al (2013c). It also might be probably ascribed to the dissociation of macromolecular protein by ultrasound during heating (Dong et al 2011). This was in accord with the results of Jambrak et al (2009) who had already reported that ultrasonic pretreatments could change the particle size of proteins.…”
Section: Particle Sizesupporting
confidence: 79%
“…Studies of the hydrophilicity of rapeseed protein with a mixture of albumine and globuline have shown a great hydrophilicity compared to isolated albumine or globuline fraction [43]. Ultrafiltrated rapeseed protein has a better solubility than the protein which is acid-precipited [44]. This is supported by another examination of rapeseed protein, in which the isolates show a low solubility of 26 % at pH 9, in contrast to ultrafiltrated protein, which exhibit a solubility of 90 %.…”
Section: Protein Solubilitymentioning
confidence: 92%
“…Besides, the FC of the sample depends directly on its soluble protein fraction and the presence of other components (e.g., fiber). They also play a useful role by improving the surface viscosity and promoting the formation of a stable foam [44]. The FC and FS of the RPC-A show a different behavior in comparison to the unmodified protein samples since their FC is the highest of all protein samples, but their FS is the lowest.…”
Section: Foaming Capacitymentioning
confidence: 99%
See 1 more Smart Citation
“…Cruciferin and napin constitute roughly 70 % and 30 % of the total protein, respectively [10][11][12]. Cruciferin (12 S; molecular mass~240-300 kDa) is a saltsoluble globulin with a isoelectric point (pI) of~7.2 [13], and is comprised of high level of β-sheets (~50 %) and low level of α-helices (~10 %) [14].…”
Section: Introductionmentioning
confidence: 99%